Fast-Charging Techniques for Electric Vehicle Batteries - Alok Kumar; Atul Kumar Yadav (International Journal of Electrical and Communication Engineering Technology, 2026)
EVs (Electric Vehicles) are becoming the popular mode of green transport, boosted by their efficiency, lower emission and technological vibrancy. But slow battery charging still poses one of the primary stumbling blocks to EV deployment. Conventional charging methods that take hours necessitate inconvenience and range- anxiety. To tackle this, scientists and companies are in a race to develop fast-changing technologies that can charge batteries within minutes without compromising safety. These systems need to address issues such as thermal rise, lithium plating and degradation at high- current charging. State-of-charge (SoC) estimate accuracy, aging effects, charging time reduction, thermal behavior, and implementation complexity are all compared amongst these charging approaches in this research. Electrochemical constraints that limit ultra-fast charging capabilities—such as lithium plating, thermal runaway dangers, degradation mechanisms, and safety restrictions—are given particular consideration. The study also discusses new developments in EV charging infrastructure, such as vehicle-to-grid (V2G) technology, bidirectional charging systems, smart grid integration, and high-power DC fast-charging stations. A review of different fast-charging approaches for EVs lithium-ion batteries is the focus of this paper. It covers the principal charging schemes, including CC–CV, multistage- style, pulse-based method or model-predictive and AI-guided bill-to-plug. The paper also introduces some challenges, safety limits and recent developments in EV charging stations and infrastructure. The review is concluded by proposing some areas for future research in solid- state batteries, ultra-fast charging and AI motion energy management.
Keywords: AI-Powered Charging; Battery Health; EV Infrastructure; electric vehicles; fast charging; lithium-ion batteries